Nordic survey on assessment and treatment of fluid overload in intensive care - Zeuthen, Emilie; Wichmann, Sine; Schønemann-Lund, Martin; Järvisalo, Mikko J.; Rubenson-Wahlin, Rebecka; Sigurðsson, Martin I.; Holen, Erling; Bestle, Morten H. (Frontiers in Medicine, 2022)
Introduction: Fluid overload in patients in the intensive care unit (ICU) is associated with higher mortality. There are few randomized controlled trials to guide physicians in treating patients with fluid overload in the ICU, and no guidelines exist. We aimed to elucidate how ICU physicians from Nordic countries define, assess, and treat fluid overload in the ICU. Methods: We developed an online questionnaire with 18 questions. The questions were pre-tested and revised by specialists in intensive care medicine. Through a network of national coordinators. The survey was distributed to a wide range of Nordic ICU physicians. The distribution started on January 5th, 2022 and ended on May 6th, 2022. Results: We received a total of 1066 responses from Denmark, Norway, Finland, Sweden, and Iceland. When assessing fluid status, respondents applied clinical parameters such as clinical examination findings, cumulative fluid balance, body weight, and urine output more frequently than cardiac/lung ultrasound, radiological appearances, and cardiac output monitoring. A large proportion of the respondents agreed that a 5% increase or more in body weight from baseline supported the diagnosis of fluid overload. The preferred de-resuscitation strategy was diuretics (91%), followed by minimization of maintenance (76%) and resuscitation fluids (71%). The majority declared that despite mild hypotension, mild hypernatremia, and ongoing vasopressor, they would not withhold treatment of fluid overload and would continue diuretics. The respondents were divided when it came to treating fluid overload with loop diuretics in patients receiving noradrenaline. Around 1% would not administer noradrenaline and diuretics simultaneously and 35% did not have a fixed upper limit for the dosage. The remaining respondents 63% reported different upper limits of noradrenaline infusion (0.05 to 0.50 mcg/kg/min) when administering loop diuretics. Conclusion: Self-reported practices among Nordic ICU physicians when assessing, diagnosing, and treating fluid overload reveals variability in the practice. A 5% increase in body weight was considered a minimum to support the diagnosis of fluid overload. Clinical examination findings were preferred for assessing, diagnosing and treating fluid overload, and diuretics were the preferred treatment modality.